Accounting Models for Insurer’s Capital Management - Nachkova, Maya (Research Papers, 2005)
The purpose of the present thesis is to improve the theoretical-methodological and organizational aspects of the insurers’ accounting and capital management models and to set them in line with the contemporary analysis requirements and with the processes of integration and globalization of insurance worldwide, taking into account the national and foreign expertise in the theory and practice of insurance and accounting. The methods of the study have been presented from the positions of the systematic approach by investigating, analyzing and evaluating the existing models and proposing new ones of insurers’ capital accounting for. Insurance product cost formation accounting models and regression income and reinsurance fees & commission accounting ones have been developed. A model for determining the insurers’ capital needs have been proposed. Insurers’ solvency zone has been formulated investigating its components and boundaries. Specific instructions for improvement of the forms of investing capital have been defined for the purpose of improving its profitability and a model for the investment risk management through diversification of the insurers’ investment portfolio has been presented.